2007
DOI: 10.1017/s1481803500015463
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department patient compliance with follow-up for outpatient exercise stress testing: a randomized controlled trial

Abstract: Introduction:Numerous patients are assessed in the emergency department (ED) for chest pain suggestive of acute coronary syndrome (ACS) and subsequently discharged if found to be at low risk. Exercise stress testing is frequently advised as a follow-up investigation for low-risk patients; however, compliance with such recommendations is poorly understood. We sought to determine if compliance with follow-up for exercise stress testing is higher in patients for whom the investigation is ordered at the time of ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 12 publications
0
29
1
1
Order By: Relevance
“…La adherencia a este proceso de atención fue incompleta debido a que solo al 45,4% de los pacientes se les realizó la prueba diagnóstica ambulatoria. El estudio de Richards et al 30 reportó mayores promedios de cumplimiento de la prueba diagnóstica y de la cita de valoración por cardiología, cuando la prueba fue agendada previo al alta del paciente. Este no fue siempre posible en nuestra muestra de pacientes.…”
Section: Discussionunclassified
“…La adherencia a este proceso de atención fue incompleta debido a que solo al 45,4% de los pacientes se les realizó la prueba diagnóstica ambulatoria. El estudio de Richards et al 30 reportó mayores promedios de cumplimiento de la prueba diagnóstica y de la cita de valoración por cardiología, cuando la prueba fue agendada previo al alta del paciente. Este no fue siempre posible en nuestra muestra de pacientes.…”
Section: Discussionunclassified
“…Compliance rates improve significantly when outpatient stress tests are organised prior to discharge, Meyer demonstrated a 92.2% compliance rate for EST when the procedure was booked prior to discharge, and Richards showed that compliance improved from 56.1% for patients advised to see their PCP to organise the procedure, to 72.5% for patients who had their EST booked prior to discharge 2 17. The efficacy of this strategy is based on the premise that the fewer steps an individual must take to reach a goal, the more likely they are to complete it.…”
Section: Discussionmentioning
confidence: 99%
“…Research CMAJ OPEN been reported for older patients who have visited emergency departments (regardless of need for follow-up), 35 with better rates (73%) among patients with chest pain who were directly referred for a stress test. 36 The patient with newly diagnosed atrial fibrillation who has not received follow-up care is likely to have gone unprotected from a stroke; however, the risk is …”
Section: Comparison With Other Studiesmentioning
confidence: 99%